Spiritual Sobriety in 1 Peter - Watson, David. F. 1970- (2011)
1 Peter encourages believers to adhere to Christian teachings, community, and norms of behavior in the face of suffering and conflict with the dominant culture. In 1 Peter’s schema, Christians suffer largely because non-Christians are unaware of God’s saving work in Jesus Christ and the special status that God has bestowed upon the faithful. In three instances (1:13; 4:7; 5:8), 1 Peter calls believers to “be sober.” These are not simply exhortations to be alert in light of the coming judgment. Those who are sober know of the salvation offered to them in Jesus Christ and base their hope on it. They view their circumstances in light of the truths of their faith, and therefore see the world around them differently than those who do not share their beliefs. The exhortation to sobriety, then, is not just a call to action, but to proper belief. Their worldview as Christians is the basis of their motivation to remain both in association and conduct within the Christian community. Christians today can take from these admonitions the reminder that the truths of our faith precede the living out of our faith. Catechesis precedes mission. Knowledge of the truths of our faith is part of what forms our view of the world and helps us to live as we should.
Keywords: 1 Peter; Bible. New Testament -- Criticism, interpretation, etc; Bible. Peter, 1st; Catechesis; Christians; God; Honor; Jesus Christ; Jesus Christ -- Teachings -- Meditations; Meditations; Persecution; Shame; sober; Sobriety; Suffering; Teachings